The Preliminary Evaluation Study of the Indonesian Housing Subsidy Program in 2010-2019 - Cindar Hari Prabowo; Joko Adianto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This preliminary study aims to evaluate the contribution of the FLPP program to cope with the accelerating housing backlog, as one of the prominent subsidized housing programs. It also attempts to identify one of the key factors to its contribution level. Although many subsidized housing programs have been launched by the Government of Indonesia, the number of homeownerships is still outpaced by the surmounting housing backlog. However, their evaluation remains to receive a little attention to refine the similar programs in the future. By employing a descriptive analysis on the FLPP data series from 2010-2019, this study finds a heartbreaking level of contribution of the FLPP program to the housing backlog alleviation, due to increasing housing price which implicates the ratio of housing affordability and the deviation of the designated beneficiaries. Innovation in affodable housing construction and design are urgently required to maintain the ratio of housing affordability from the housing stress for the low incomes as the designated beneficiaries.